Can interventions that aim to decrease Lyme disease hazard at non-domestic sites be effective without negatively affecting ecosystem health? A systematic review protocol. Issue 1 (December 2016) - Middleton, Jo; Cooper, Ian; Rott, Anja
Abstract Background Lyme disease (LD) is the most commonly reported, broadly distributed vector-borne disease of the northern temperate zone. It is transmitted by ticks and, if untreated, can cause skin, cardiac, nervous system and musculoskeletal disease. The distribution and incidence of LD is increasing across much of North America and Western Europe. Interventions to decrease exposure to LD hazard by encouraging behavioural change have low acceptance in high risk groups, and a safe, effective human LD vaccine is not presently available. As a result, habitat level interventions to decrease LD hazard itself (i.e. levels of infected ticks) have been proposed. However, some interventions may potentially negatively affect ecosystem health, and consequentially be neither desirable, nor politically feasible. This systematic review will catalogue interventions that aim to reduce LD hazard at non-domestic sites, and examine the evidence supporting those which are unlikely to negatively affect ecosystem health. Methods The review will be carried out in two steps. First, a screening and cataloguing stage will be conducted to identify and characterise interventions to decrease LD hazard at non-domestic sites. Secondly, the subset of interventions identified during cataloguing as unlikely to negatively affect ecosystem health will be investigated. In the screening and cataloguing step literature will be collected through database searching using pre-chosen search strings, hand-searching key journals and reviewing the websites of public health bodies. Further references will be identified by contacting stakeholders and researchers. Article screening and assessment of the likely effects of interventions on ecosystem health will be carried out independently by two reviewers. A third reviewer will be consulted if disagreements arise. The cataloguing step results will be presented in tables. Study quality will then be assessed independently by two reviewers, using adapted versions of established tools developed in healthcare research. These results will be presented in a narrative synthesis alongside tables. Though a full meta-analysis is not expected to be possible, if sub-groups of studies are sufficiently similar to compare, a partial meta-analysis will be carried out.